Biological Activities of Extracellular Vesicles and Their Cargos from Bovine and Human Milk in Humans and Implications for Infants1–. Issue 1 (16th November 2016) - Zempleni, Janos; Aguilar-Lozano, Ana; Sadri, Mahrou; Sukreet, Sonal; Manca, Sonia; Wu, Di; Zhou, Fang; Mutai, Ezra
Abstract: Extracellular vesicles (EVs) in milk harbor a variety of compounds, including lipids, proteins, noncoding RNAs, and mRNAs. Among the various classes of EVs, exosomes are of particular interest, because cargo sorting in exosomes is a regulated, nonrandom process and exosomes play essential roles in cell-to-cell communication. Encapsulation in exosomes confers protection against enzymatic and nonenzymatic degradation of cargos and provides a pathway for cellular uptake of cargos by endocytosis of exosomes. Compelling evidence suggests that exosomes in bovine milk are transported by intestinal cells, vascular endothelial cells, and macrophages in human and rodent cell cultures, and bovine-milk exosomes are delivered to peripheral tissues in mice. Evidence also suggests that cargos in bovine-milk exosomes, in particular RNAs, are delivered to circulating immune cells in humans. Some microRNAs and mRNAs in bovine-milk exosomes may regulate the expression of human genes and be translated into protein, respectively. Some exosome cargos are quantitatively minor in the diet compared with endogenous synthesis. However, noncanonical pathways have been identified through which low concentrations of dietary microRNAs may alter gene expression, such as the accumulation of exosomes in the immune cell microenvironment and the binding of microRNAs to Toll-like receptors. Phenotypes observed in infant-feeding studies include higher Mental Developmental Index, Psychomotor Development Index, and Preschool Language Scale-3 scores in breastfed infants than in those fed various formulas. In mice, supplementation with plant-derived MIR-2911 improved the antiviral response compared with controls. Porcine-milk exosomes promote the proliferation of intestinal cells in mice. This article discusses the above-mentioned advances in research concerning milk exosomes and their cargos in human nutrition. Implications for infant nutrition are emphasized, where permitted, but data in infants are limited.